Był by ktoś tak miły i rozwiązał mi to ?
.Usun nawiasy i wykonaj redukcję wyrazów podobnych.
a) 7(3a-2b)+4(8b-a)=
b)5(x-3y+2)+ 9 (-5x+4y - 3) =
c)6(4p-7r)-2(8p-9r)=
d)-8(-3m+9p+2)-5(6m-6p-9)=
e)4(4a-7b)-7(3a-5b)-2(6b-5a)=
f)0,5(8x-12y)+0,6(5x-15y)=

3

Odpowiedzi

2010-02-10T18:15:31+01:00
A). 21a-14b+32b-4a
17a+18b
b). 5x-15y+10-45x+36y-27
-40x+21y-17
c). 24p-42r-16p+18r
8p-24r
d). 24m-72p-16-30m+30p+45
-6m-42p+29
e). 16a-28b-21a+35b-12b+10a
5a-5b
f). 4,5x-6y+3x-9y
7,5x-3y
2010-02-10T18:17:17+01:00
A) 7(3a-2b)+4(8b-a)= 21a-14b+32b-4a=17a+18b
b)5(x-3y+2)+ 9 (-5x+4y - 3) =5x-15y+10-45x+36y-27=-40x+21y-17
c)6(4p-7r)-2(8p-9r)=24p-42r-16p+18r=8p-24r
d)-8(-3m+9p+2)-5(6m-6p-9)=24m-72p-16-30m+30p+45=-6m-42p+39
e)4(4a-7b)-7(3a-5b)-2(6b-5a)=16a-28b-21a+35b-12b+10a=5a-5b
f)0,5(8x-12y)+0,6(5x-15y)= 4x-6y+3x-9y=7x-15y
Najlepsza Odpowiedź!
2010-02-10T18:20:14+01:00
A) 7(3a-2b)+4(8b-a)=21a-14b+32b-4a=17a+18b
b)5(x-3y+2)+9(-5x+4y-3)=5x-15y+10-45x+36y-27=-40x+21y-17
c)6(4p-7r)-2(8p-9r)=24p-42r-16p+18r=8p-24r
d)-8(-3m+9p+2)-5(6m-6p-9)=24m-72p-16-30m+30p+45=-6m-42p+29
e)4(4a-7b)-7(3a-5b)-2(6b-5a)=16a-28b-21a+35b-12b+10a=5a-5b
f)0,5(8x-12y)+0,6(5x-15y)=4x-6y+3x-9y=7x-15y